Lactoferrin Against SARS-CoV-2: In Vitro and In Silico Evidences - Elena Campione; Caterina Lanna; Terenzio Cosio; Luigi Rosa; Maria Pia Conte; Federico Iacovelli; Alice Romeo; Mattia Falconi; Claudia Del Vecchio; Elisa Franchin; Maria Stella Lia; Marilena Minieri; et al. (Frontiers Media S.A., 2021)
Lactoferrin (Lf) is a cationic glycoprotein synthetized by exocrine glands and is present in all human secretions. It is also secreted by neutrophils in infection and inflammation sites. This glycoprotein possesses antimicrobial activity due to its capability to chelate two ferric ions per molecule, as well as to interact with bacterial and viral anionic surface components. The cationic features of Lf bind to cells, protecting the host from bacterial and viral injuries. Its anti-inflammatory activity is mediated by the ability to enter inside the nucleus of host cells, thus inhibiting the synthesis of proinflammatory cytokine genes. In particular, Lf down-regulates the synthesis of IL-6, which is involved in iron homeostasis disorders and leads to intracellular iron overload, favoring viral replication and infection. The well-known antiviral activity of Lf has been demonstrated against DNA, RNA, and enveloped and naked viruses and, therefore, Lf could be efficient in counteracting also SARS-CoV-2 infection. For this purpose, we performed in vitro assays, proving that Lf exerts an antiviral activity against SARS-COV-2 through direct attachment to both SARS-CoV-2 and cell surface components. This activity varied according to concentration (100/500 μg/ml), multiplicity of infection (0.1/0.01), and cell type (Vero E6/Caco-2 cells). Interestingly, the in silico results strongly supported the hypothesis of a direct recognition between Lf and the spike S glycoprotein, which can thus hinder viral entry into the cells. These in vitro observations led us to speculate a potential supplementary role of Lf in the management of COVID-19 patients.